Perspectives: The Burden of Proving Burnout in Academic Library Workers - Matthew Johnson; Sylvia Page (Canadian Journal of Academic Librarianship)
Current paradigms of assessment, measurement, and evidence-based practice in libraries, which inform administrative and managerial action (or inaction), construct an undue burden of proof for burnout (and other negative workplace conditions) that denies library workers the care and interventions necessary for them to thrive in their workplace and that leads to continued exploitative practices and emotional extraction.